Design and validation of two tools to observe and analyze history lessons in secondary education - Miralles-Sánchez, Pedro; Gómez-Carrasco, Cosme J.; Rodríguez-Medina, Jairo (Frontiers in Education, 2023)
This article focuses on the validation of two data collection instruments, one is the History Class Observation Tool (HCOT) and the other is focus groups with students, trainee teachers and tutors from secondary school classrooms. The main objective of the study is to obtain evidence of validity of the two instruments to be used in research on the design, validation, implementation, and evaluation of training units. All this in order to improve the teaching-learning process of historical thinking skills in high school students with the aim of forming critical citizens. The initial set of 32 observable behaviours was reviewed by 9 judges, who rated each on a scale of 0 (strongly disagree) to 3 (strongly agree) in terms of appropriateness, importance, clarity of wording, and observability. As can be seen from the results, both instruments according to the agreement indices suggest that the items, overall, can be considered suitable and important, and observable in the case of the observation instrument, as well as having clarity of wording appropriate to the objectives of both, with high confidence on the part of the experts. If we compare it with similar studies that we have discussed previously, we can see how this validation process has been quite rigorous and novel following some guidelines set previously in certain studies.